ANALYZING THE EFFECT OF WORK DISCIPLINE AND EMPLOYEE MORALE ON EMPLOYEE PERFORMANCE PT. BANK SULUTGO - Oley, Roen F.; Saerang, David P.E; Pandowo, Merinda . (FEB Universitas Sam Ratulangi Manado, 2019)
Abstract: Work discipline can be interpreted where the employee himself can correct the lack of behavior and ensure compliance with company rules that have been established. The purpose of the discipline applied in every company or organization is the correct behavior. In general employee discipline should be limited such as the release of warning letters, though letters or actual termination. Therefore, to improve performance, employees must be able to comply with regulations such as always coming to work at the right time or can also do their work diligently or well dress in the office so that employees can work effectively. This research aims to analyze the effect of work discipline and employee morale on employee performance in company. This research is using quantitative research with multiple linear regression. This research based on numeric figures or numbers. Population in this research are all employee at bank. The result of this research shows that the work discipline and employee morale have a significant effect to employee performance. The bank leaders should pay more attention to employee morale and employee discipline so that they can improve the quality of the company.Â Keywords: human resources management, work discipline, employee morale, employee performanceÂ